A new method for the redundancy analysis of Petri net-based liveness enforcing supervisors. (May 2017) - Gelen, Gökhan; Uzam, Murat; Li, ZhiWu
The deadlock control of flexible manufacturing systems (FMSs) has been widely studied in the literature. Petri nets (PNs) are extensively used as a tool for modelling, analysis and controller synthesis of such systems. In general, Petri-net-based liveness enforcing supervisors (LESs) include control places ( CP s) together with their input/output arcs. It is well known that the methods proposed for computing CP s may provide redundant and necessary CP s. In this paper, a new method is proposed for redundancy test of CP s by means of supervisory control theory (SCT). The proposed method is based on the idea that after the removal of a CP from an LES, if the controlled model is still live, then the removed CP is redundant. The proposed method makes use of the TCT implementation tool of SCT. It is applicable to a PN-based LES consisting of a set of CP s. The applicability of proposed method is demonstrated by means of examples from the relevant literature. For some examples, the redundancy test provides more permissive behaviour with structurally simpler supervisors.